Blended E-Learning Management System for the Technological University Graduate Programs - Rolluqul, Gisela V. (INTI International University, 2011)
The Technological University of the Philippines as the premier technology Education University of the Country, offers graduate programs in different areas in technology and engineering. Professionals both from the academe and the industry who want to upgrade themselves through higher education choose the Technological University of the Philippines. However, due to work schedule and distance, the students cannot attend regular classes in the university. The University oilers extension classes wherein the professors go to a consortium university to teach in the off-campus graduate programs but this created a lack of manpower in the campus. Thus, to lessen the problem of manpower and at the same time cater to a much wider populace, an E- Learning system for the graduate programs of the University was developed. The system evolved to a blended system, synchronous and asynchronous, to make it more interactive and in real-time for those who can afford to be online while the class is in session. First, a study was done on the capability of the University to offer E-Learning system In terms of resources and technology. Further, before the actual design and development of the system, a study was conducted on the existing systems available in the country as well as these used in other countries. After these studies the Blended E-Learning Management system was developed and initially tested. Modules for the system are being developed to further test the system and its interactivity. The results of the tests showed that the system is very satisfactorily functioning as designed and can be implemented in the coming school year, 2011-2012, for some basic subjects In the Graduate Programs of the University.